Retention in Care within 1 Year of Initial HIV Care Visit in a Multisite US Cohort: Who's In and Who's Out?. (May 2014) - Tedaldi, Ellen M.; Richardson, James T.; Debes, Rachel; Young, Benjamin; Chmiel, Joan S.; Durham, Marcus D.; Brooks, John T.; Buchacz, Kate; ,
Biannual attendance at medical visits is an established measure of retention in HIV care. We examined factors associated with attending at least 2 clinic visits at least 90 days apart among HIV-infected, antiretroviral therapy (ART)-naive HIV Outpatient Study participants entering care during 2000 to 2011. Of 1441 patients, 85% were retained in care during the first year of observation. Starting ART during the year was the strongest correlate of retention (adjusted odds ratio [aOR] 6.4, 95% confidence interval [CI] 4.4-9.4). After adjusting for starting ART, publicly insured patients (aOR 0.6, 95% CI 0.4-1.0), and patients with baseline CD4 counts <200 cells/mm 3 (aOR 0.5, 95% CI 0.3-0.9) or missing CD4 counts (aOR 0.3, 95% CI 0.2-0.6) were less likely to be retained in care. Although most patients had recommended biannual care visits, some ART-naive individuals may require additional interventions to remain in care. Promptly initiating ART may facilitate engagement in care.